IMPLEMENTATION OF AN INDEPENDENT LEARNING CURRICULUM IN ENHANCING STUDENT CREATIVITY IN PRIMARY SCHOOLS - Rafika Nisa; Marzaniatun; Farida Hanum; Al-Amin (Indonesian Journal of Education (INJOE), 2024)
The global education era has undergone a transformation in which educators and policymakers are increasingly emphasising the need for creative and independent thinkers in the 21st century. Therefore, the Implementation of Merdeka Belajar Curriculum in elementary schools emerges as a key strategy to foster creativity among learners. The study in this research uses the literature research method. The results showed that; First, Merdeka Belajar Curriculum contributes to the development of student creativity by providing opportunities to engage in independent learning, critical thinking, and problem-solving activities. Second, this curriculum also encourages students to explore their interests and passions, which in turn stimulates their creative thinking process. Therefore, teachers should facilitate this learning environment by providing guidance, support and resources that enable students to take charge of their learning journey. Third, every time the curriculum changes, new challenges arise, such as the implementation of the Merdeka Belajar curriculum. Such challenges include the need for teacher training in innovative teaching strategies, the need for sufficient resources, and overcoming traditional educational practices that may hinder the adoption of more progressive approaches.